The effect of maturated stages and soaking treatment of water and GA3 hormone on Brucea javanica (L.) Merr germination - NINIK SETYOWATI; NING WIKAN UTAMI (Society for Indonesian Biodiversity, 2008)
Research on the effect of maturated stages and soaking treatment of water and Giberrelic Acid hormone on Brucea javanica germination was carried out at Macropropagation Laboratory, Research Centre of Biology, LIPI, Cibinong-Bogor. The research study arranged by Factorial in Completely Randomized Design with 2 factors and 3 replications, each replication with 20 seeds sample. The first factor was maturated stage of fruits with 3 levels factor i.e. green, brown and black peels, and the second factor was soaking treatment with 6 levels factor i.e. 0 (control), 1, 3 days in water, 500, 1000, 1500 mg/L in GA3 solution. The results showed that the maturated stage had significant on seeds germination of B. javanica. The black peel of maturated stage of fruit was the best factor on chosen on B. javanica seedling, in comparing with brown and green peels. Soaking treatment in GA3 solution was effective on trigger of seeds germination of B. javanica. The combination treatment of black peel maturated stage with 1500 mg/L GA3 solution were the best result for all parameter observation i.e. on the first germination (4 days), rich germination 50% (10 days), germination percentage (93.33%) and germination value (7.074). But in the control were first germination (10 days), rich germination only 20% (no rich 50%), germination percentage (93.33%) and germination value (0.148).Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: maturity stages, soaking, water, GA3, seeds germination, Brucea javanica (L.) Merr